A novel flex sensor-based flexible smart garment for monitoring body postures - Abro, Zamir Ahmed; Yi-Fan, Zhang; Nan-Liang, Chen; Cheng-Yu, Hong; Lakho, Rafique Ahmed; Halepoto, Habiba (Journal of industrial textiles, 2019)
Posture monitoring and investigation in wearable technology play a significant role in the analysis of body postures. This study aims to develop a new flexible smart garment realized by stitching flex sensors at different joint positions for sensing flexion angles in static and kinematic motions. Calibration tests were conducted by systematically flexing wrist, elbow, and knee joints, respectively. A male subject then wore the developed flexible smart garment to sense different body postures. The measured data from flex sensors inside the smart garment exhibited immediate response after each joint movement of the male subject. The minimum measurement sensitivities of flex sensors mounted at the knee, elbow, and wrist was 0.94°, 0.8°, and 0.56°, respectively. Measured flexion angle changes were within 80°, 95°, and 140° ranges from knee, elbow, and wrist. Both stand and walk tests at a velocity of 4 km/h indicate that the flexion angles of three joint positions include wrist, elbow, and knee joints can be effectively monitored using the flex sensor–based smart garment. Flex sensor can be employed to monitor body joint movement and future to identify different postures of body joints in practice. The flexible smart garments cannot be washed.